Determinants of smallholders' entrepreneurial drive, willingness and ability to expand farming operations in KwaZulu-Natal. Issue 8 (16th November 2020) - Cele, Lungelo; Wale, Edilegnaw
ABSTRACT: Government policy in South Africa to promote agricultural entrepreneurship among smallholders has failed to recognise their heterogeneity and the factors that influence their entrepreneurial drive. Furthermore, there is a lack of empirical evidence on the factors that influence smallholders' willingness and ability to expand farming operations. This study adopted multivariate general linear and ordered probit models to examine smallholders' entrepreneurial spirit. The findings suggested that the new strategic focus should aim to boost smallholder entrepreneurial drive by providing secure land use rights, access to market information and affordable irrigation systems. Policymakers must formulate enabling policies to include young women in profitable farming activities.